Hepatitis C virus infection in kidney transplantation‐changing paradigms with novel agents. (25th April 2018) - Reddy, Yuvaram N. V.; Nunes, David; Chitalia, Vipul; Gordon, Craig E.; Francis, Jean M.
Abstract: Hepatitis C virus (HCV) is a common cause of increased morbidity and mortality in kidney transplant patients. It is associated with posttransplant glomerulonephritis, chronic allograft nephropathy, and New Onset Diabetes after Transplant (NODAT). In the past, HCV was difficult to treat due to the presence of interferon alpha‐based therapies that were difficult to tolerate and were associated with adverse side‐effects, such as the risk of rejection. With the advent of oral directly acting antiviral therapies, the landscape for HCV and transplantation has changed. These agents are highly effective and well tolerated with minimal side‐effects. Sustained viral response rates in excess of 90% are achieved with most current treatment regimens active against all HCV genotypes. These new agents may show an improvement in graft and patient survival while essentially eliminating the risk of acute rejection from the use of prior interferon‐based HCV therapies. These agents may also result in an improvement in organ allocation for HCV donor/HCV recipient transplantation. This review is meant to discuss the epidemiology of HCV, the new oral direct‐acting antiviral agents (DAAs) and future opportunities for research in the field of HCV related transplantation.